Plasma Fibulin-1 Is Linked to Restrictive Filling of the Left Ventricle and to Mortality in Patients With Aortic Valve Stenosis - Dahl, Jordi S. (Blackwell Publishing Ltd, 2012)
BACKGROUND: Plasma fibulin-1 levels have been associated with N-terminal pro–B-type natriuretic peptide levels and left atrial size and shown to be predictive of mortality in patients with diabetes. The mechanisms behind these connections are not fully understood but are probably related to its roles as an extracellular matrix protein in cardiovascular tissues. METHODS AND RESULTS: One hundred twenty-five patients with severe aortic stenosis who were scheduled for aortic valve replacement (AVR) were evaluated with preoperative echocardiography and their plasma fibulin-1 levels were determined with ELISA. The cohort was followed for a median of 4 years after AVR. Increased restrictive left ventricular (LV) filling pattern was observed with increased plasma fibulin-1 levels (2% versus 29% versus 24% in low, middle, and high plasma fibulin-1 tertile groups, P=0.004). Likewise, reduced longitudinal systolic LV function (6.6±1.1 versus 6.1±1.3 versus 5.7±1.5 cm/s, P=0.05) and increased LV filling pressures was systolic velocity of the mitral annulus observed with increasing plasma fibulin-1 concentrations (ratio of early transmitral flow velocity to early diastolic flow velocity of the mitral annulus 13±4 versus 15±5 versus 16±6 in the fibulin-1 tertile groups, P=0.04). CONCLUSIONS: In patients with symptomatic severe aortic stenosis undergoing AVR, plasma fibulin-1 is associated with restrictive filling of the LV, decreased longitudinal systolic function of the LV, and increased LV filling pressures. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrial.gov with Identifier: NCT00294775